Evaluation of In-vitro Anticancer Activity and Quantitation of Active Ingredient of Adansonia digitata L. Fruit (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
In the world cancer is the major cause of death. Adansonia digitata L is commonly called as baobab belongs to Family Bombacaceae. Due to the high cost and toxic side effects like Bone marrow suppression, hepatotoxicity, nephrotoxicity, Immunosuppression, teratogenicity etc. of chemotherapeutic agents. So, for the proper controlling on cancer the trends of people are moving towards natural therapies. In light to above, in present research A. digitata L is selected for evaluation of in-vitro anticancer activity based on its reported phytoconstituents of fruit and quantitation of active principle of it. The extracts of fruit pulp, seed, and its combination were obtained using solvents like water, ethanol and n-hexane by maceration technique (Aqueous) and Soxhlet extraction method (organic). This extracts were used for further research possesses phytochemical constituents like Carbohydrates, tannins, Saponins, vitamins, alkaloids, terpenoids, phenol, glycoside flavonoids, steroids, etc. in-vitro antioxidant activity were evaluated via free scavenging assay by using DPPH assay method. Further in-vitro anticancer activity was evaluated against three human cancer cell lines MCF-7 (breast cancer cell line), Hep-G2 (liver cancer cell line) and COLO-205 (colon cancer cell line) using Brine Shrimp Lethality Assay (BSLA), Tryphan Blue Dye Cell Exclusion Assay (TBDCEA) and MTT assay. The quantitation of active ingredients Vit. C and Squalene from extracts was done by using titration method and HPLC method respectively. Formulation possesses highest percent antioxidant capacity (49.36). In BSLA formulation possesses highest rate of percent mortality than other extracts. In TBCE assay and in MTT assay formulation gives more significant effect in Hep-G2 liver cancer cell line than remaining cell lines. These findings introduce A. digitata L as potentially useful as anti-cancer agent. Further research is required to elucidate its specific mechanism of action and exact active principle responsible for action.